Group Strengthening Education and Farming Science in Empowering KWT Sawung Martani - Ulfah Nurdiana; Akhmad Rizqul Karim; Alpha Nadeira Mandamdari; Wahyu Adhi Saputro; Dewanti Risa Utami (Universitas Veteran Bangun Nusantara, 2025)
Empowerment can be done through women's groups that exist in an area. One of the right forums is a women's farmer group. KWT Sawung Martani is a women's farmer group that exists in Banyumas Regency. Based on the analysis of the problem situation, there are two main problems in KWT Sawung Martani, namely the lack of group activity and the ignorance of group members regarding the profits and losses of the plant cultivation they are carrying out. This community service activity aims to provide education on group strengthening and agricultural business knowledge in empowering KWT Sawung Martani. The activity method used is education through extension activities. Based on the activities carried out, each member of KWT Sawung Martani has fully understood the education and materials provided by the community service team. That way, in the future, the implementation of group strengthening will strengthen solidarity and the development of a group must be carried out dynamically so that the group can run independently later KWT Sawung Martani and the application of agricultural business knowledge will make cultivation activities in KWT Sawung Martani more efficient.